1997
DOI: 10.1097/00007632-199706150-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between the Boston Brace and the Charleston Bending Brace in Adolescent Idiopathic Scoliosis

Abstract: When given the choice between these two orthoses in the treatment of adolescent idiopathic scoliosis, the authors recommend use of the Boston brace. The Charleston brace should be considered only in the treatment of smaller single thoracolumbar or single lumbar curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 28 publications
2
90
2
Order By: Relevance
“…Some authors [21] evaluated the effectiveness of performing personality tests for patients with idiopathic scoliosis who underwent brace therapy and concluded that these tests are useful for evaluating psychological effects and ensuring continuation of therapy minimizing patient dropout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [21] evaluated the effectiveness of performing personality tests for patients with idiopathic scoliosis who underwent brace therapy and concluded that these tests are useful for evaluating psychological effects and ensuring continuation of therapy minimizing patient dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Bracing has been established as the most effective nonoperative treatment for adolescences with mild idiopathic scoliosis and Scheuermann kyphosis [21,29].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded the Wilmington brace favorably altered the natural history of 20°to 39°V curves. Katz et al [25] reviewed 51 patients who had average curves sizes of 36°to 45°treated with the Boston brace. Treatment was successful in 61% of patients, although 16% progressed more than 5°and 31% required surgery.…”
Section: Bracing Efficacymentioning
confidence: 99%
“…Likewise, the probability brace treatment will prevent curve progression is inversely proportional to the initial size of the curve [11,25,30]. Although brace treatment limits curve progression for curves larger than 35°, success has been less predictable compared with curves between 20°and 35° [1,11,25,30].…”
Section: Bracing Difficultiesmentioning
confidence: 99%
“…Several uncontrolled retrospective case series of braced patients have been published; those reporting surgical rates demonstrate widely varying outcomes ranging from 7% to 43%. [10][11][12][13][14][15][16][17][18][19][20][21][22] Two studies have simultaneously compared untreated and braced curves. 2,3 Fernandez-Feliberti et al 2 reported a 26% surgery rate in the braced cases compared with 38% in the observed cases.…”
mentioning
confidence: 99%